Study of Blood Polymorphism of Kerinci Duck - Nur, H.; Yusrizal , Y.; Manin, F. (International Journal of Poultry Science, 2012)
Knowing genetic potential of duck would give a better understanding on proper rearing management for efficient production. There is still lacking information of genetic data base of Kerinci ducks, one of indigenous productive-layer type ducks in Indonesia. A study was conducted in Jambi Province, Indonesia and aimed at elucidating blood protein profile and evaluating genetic diversity of Kerinci ducks. The results showed three kinds of blood protein, namely transferin, post-transferin 1 and post-transferin 2. Albumin was not detected in the blood. Polymorphism was only detected in transferin locus. Gene frequency in the locus of post-transferin 1 and post-transferin 2 was recognized as A gene. Both genes A and B were seen in the locus of transferin with A being dominant. Data indicated highly genetic similarity of Kerinci Ducks which potentially gives similar phenotypic potential among them.